A Modern History of Fiscal Prudence and Profligacy - Mauro, Paolo (International Monetary Fund, 2013)
We draw on a newly collected historical dataset of fiscal variables for a large panel of countries-to our knowledge, the most comprehensive database currently available-to gauge the degree of fiscal prudence or profligacy for each country over the past several decades. Specifically, our dataset consists of fiscal revenues, primary expenditures, the interest bill (and thus both the primary and the overall fiscal deficit), the government debt, and gross domestic product, for 55 countries for up to two hundred years. For the first time, a large cross country historical data set covers both fiscal stocks and flows. Using Bohn's (1998) approach and other tests for fiscal sustainability, we document how the degree of prudence or profligacy varies significantly over time within individual countries. We find that such variation is driven in part by unexpected changes in potential economic growth and sovereign borrowing costs